A behavioral cultural-based development analysis of entrepreneurship in China - Yue Dai (Administrative Sciences, 2021)
This paper deals with local cultural capital as a motivator for entrepreneurial behavior in China. Following the Culture-Based Development paradigm (CBD), the current study approaches local cultural capital as an entity that can be temporarily segmented into living culture and cultural heritage and can be further differentiated type-wise into material cultural capital and immaterial cultural capital. The main hypothesis of this paper is that living culture and cultural heritage have different roles in the direction of effect on entrepreneurial behavior in China. To test this hypothesis, a quantitative research method is utilized and data is collected from China Statistical Yearbooks, the website of Chinese Intangible Cultural Heritage as well as the third and fourth China Economic Census Yearbooks, covering the period from 2010 to 2019 and regarding all 31 provinces of mainland China. This dataset provides indicators for both material and immaterial living culture, respectively represented by the total book circulations in public libraries and performances at art venues, while historical cultural heritage is approximated by intangible cultural heritage (such as the number of folk literature, traditional music, traditional dance and so on) and historical sites. For data analysis, an OLS regression is used to assess the roles of each kind of cultural capital on regional entrepreneurship development. Findings suggest CBD is applicable for analyzing entrepreneurship behavior and the result of the application of model shows a notable impact of culture on entrepreneurship activities in China.
Keywords: 350; China; cultural heritage; culture based development (CBD); entrepreneurship; living culture